2002
DOI: 10.1111/j.1559-1816.2002.tb01869.x
|View full text |Cite
|
Sign up to set email alerts
|

Victim Impact Testimony and Juror Judgments: The Effects of Harm Information and Witness Demeanor1

Abstract: Victim impact testimony (i.e., testimony concerning the harmful consequences on the victim's surviving family) was examined to determine its effect on the sentencing judgments of mock jurors. Undergraduate students (N= 293) watched a videotaped murder trial simulation, rendered verdicts, and made sentencing judgments. During the penalty phase of the trial, participants were either given no victim impact testimony, or they were given victim impact testimony that varied both the severity of the harm information … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 61 publications
2
44
0
2
Order By: Relevance
“…In such cases, it is possible that the influence of elevated compassion might be offset by desires to punish the source of the distress (cf. Meyers, Lynn, & Arbuthnot, 2002). However, depending upon which mechanisms underlie compassion's influence, the exact nature of the interplay of these forces is difficult to predict.…”
Section: Discussionmentioning
confidence: 98%
“…In such cases, it is possible that the influence of elevated compassion might be offset by desires to punish the source of the distress (cf. Meyers, Lynn, & Arbuthnot, 2002). However, depending upon which mechanisms underlie compassion's influence, the exact nature of the interplay of these forces is difficult to predict.…”
Section: Discussionmentioning
confidence: 98%
“…At least one other experiment revealed that this effect holds only when the victim impact statements describe more severe harm (e.g. the victim's son experienced psychological, physical, and financial distress resulting from his mother's murder) as opposed to less severe harm (e.g., the victim's son had adjusted to his mother's death well) (Myers, Lynn, & Arbuthnot, 2002). Studies reveal that more punitive judgments are especially likely when (a) the defendant is a woman (ForsterLee et al, 2004), (b) the victim impact statement contains dehumanizing language about the defendant , (c) the statement focuses on the consequences of the crime rather than on defendant characteristics (Hills & Thompson, 1999), and (d) the statements are delivered by someone who displays a high level of emotion (Nadler & Rose, 2003;Tsoudis & Smith-Lovin, 1998), because the greater emotion causes a more favorable view of the speaker (Tsoudis & Smith-Lovin, 1998).…”
Section: Victim Impact Statementsmentioning
confidence: 94%
“…It is also difficult for jurors to remain unbiased when emotionally-charged information, such as emotional testimony (including victim impact testimony) and gruesome crime scene photographs are presented (Douglas, Lyon, & Ogloff, 1997;Myers, Lynn, & Arbuthnot, 2002). The emotional testimony and gruesome photographs may possess some probative value, but they may also arouse jurors' negative emotions and consequently affect their decision.…”
Section: Introductionmentioning
confidence: 97%